Application of Raymond Fisk Model in Research of Service Quality - Eva Nedeliakova; Jana Sekulova; Ivan Nedeliak; Borna Abramovic (Communications - Scientific letters of the University of Zilina, 2016)
This article describes the results of research focused on service quality after transportation by railway freight transport. The importance of these services completes the final quality of service and has crucial importance for customers considering the future use of railway transport. The proposed algorithm of evaluation of services after transportation is based on dynamic model of Raymond Fisk. This model represents a support tool for increasing service quality in the area of railway transport.